1
$\begingroup$

So my teacher was showing us an example in class and then blasted through it during the last minutes of the class. He does not respond to his emails outside of his office hours, so I was wondering if anyone can help me out here.

We had the expression $$(P \land \lnot Q \land R) \lor (P \land \lnot Q \land \lnot R)$$ and he simplified to it $$(P \land \lnot Q) \land (R \lor \lnot R)$$ Im not sure how he got from the first step to the second. I initially thought he used Idempotent Law but Im not sure if thats true.

$\endgroup$

1 Answer 1

2
$\begingroup$

He applied Distributive Law by factoring out the $P \land \neg Q$ term from each pair of brackets. That is: $$ (A \land R) \lor (A \land \neg R) = A \land (R \lor \neg R) $$ where $A = P \land \neg Q$.

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .